Wewenang KPK Dalam Penanganan Tindak Pidana Korupsi yang Dilakukan Oleh TNI Aktif Dikaji Dari Teori Hukum Pembangunan - Telaumbanua, Yoses Ondrasi; Pangajang, Hasrudin; Busmtami, Simona (Advances In Social Humanities Research, 2023)
This study examines the authority of the KPK to perform duties and functions in terms of investigation, investigation and prosecution of corruption crimes carried out by active TNI. This research uses a normative type of research and uses a Statute Approach that examines related laws and regulations in this study, and uses a Conceptual Approach that examines legal principles or related legal principles in this study. Based on the results of research conducted by the author, it is concluded that the Corruption Eradication Commission ("KPK") has full authority to perform its duties and functions in terms of investigation, investigation and prosecution of cases of criminal acts of corruption carried out by active TNI. This is based on the principle of Equality before the law, which means that no one who is above the law, gets privileges, whether they are natives or not, come from educated groups or commoners who are illiterate, and have positions or not. Furthermore, because Article 5 of Law No. 46 concerning Corruption Courts has expressly stated the judiciary that has the authority to examine, try and decide cases of criminal acts of corruption, namely the general court in the Corruption Court. Thus overriding Law No. 31 of 1997 concerning Military Justice or applying the principle of Lex Specialis derogate Lex Generali (special law overrides general law).